PEANUTS PRODUCTION IN THE STATE OF SÃO PAULO AND ITS VIABILITY - Souza, Gabriel de Paula; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
Peanut (Arachis hypogaea L.) belongs to the Fabaceae family and is an important leguminous plant consumed worldwide. It can be used as seeds and for consumption as food. Currently, more than 90% of peanut production in Brazil is concentrated in the state of São Paulo, where planting takes place from October to November, primarily in areas of sugarcane at the time of reform. The expansion of production in the field is directly linked to new technologies, increased processing capacity and grain commercialization, mainly for the foreign market. Using bibliographical and documentary research instruments in a qualitatively applied way, we sought to demonstrate the feasibility of peanut production in the state of São Paulo, highlighting potentialities and challenges present in the production chain. Despite the many challenges to be overcome, there are great growth opportunities for all links. It could be concluded that the peanut culture has good viability and excellent return to the producer.